RETRACTED: SYNTHESIS AND CHARACTERIZATION OF ZINC GLYCEROLATE: IN VITRO TOPICAL IRRITATION, UV PROTECTION AND ANTI-MICROBIAL ACTIVITY - Cheong, Mei Yee; Abu Hassan, Hazimah; Ismail, Rosnah; Azizul Hasan, Zafarizal Aldrin (Malaysian Journal of Science, 2014)
Zinc glycerolate, has been reported to be beneficial in the treatment of many medical ailments related to skin hence it is suitable to be used in cosmetics products. Zinc glycerolate has been successfully synthesized by heating zinc oxide and glycerol in 240°C via microwave irradiation. The characterization and properties of zinc glycerolate were discussed including scanning electron microscopy (SEM), laser diffraction particle size analysis, in vitro irritancy potential, UV protection, antibacterial and permeation properties via Franz diffusion cell of the zinc glycerolate. Zinc glycerolate is classified as non-irritant when used in dermal application. It has SPF of 1.007 ± 0.004 and ultraviolet A to B (UVA/UVB) ratio of 0.7 ± 0.019 which is considered good for UVA protection under Boot’s star rating. The antimicrobial properties of zinc glycerolate were expressed as the minimum inhibitory concentration (MIC); the minimum bactericidal concentration (MBC) and the time needed to eliminate 99.9% of the bacteria population (time-kill). Zinc glycerolate has better bactericidal properties than zinc oxide particularly towards Staphylococcus epidermis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Propionibacterium acnes while no effect was observed for Candida albicans and Aspergillus niger. The concentration of zinc ions that has diffused through polysulfone membrane installed in a Franz diffusion cell was determined through Atomic Absorption Spectroscopy (AAS). The highest concentration of zinc ion diffused was found from incorporation of zinc glycerolate in oil-in-water (O/W) cream-based excipient. The obtained results indicated that zinc glycerolate has a good potential for applications in the cosmetics and pharmaceutical products.